2002
DOI: 10.3989/scimar.2002.66s2233
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of demersal fish assemblages of the Tuscany and Latium coasts (north-western Mediterranean)

Abstract: A four-year time series (1994-1997) of groundfish trawl surveys performed within the European Union Project MEDITS (Mediterranean International Trawl Surveys), was analysed to identify and describe the fish assemblages along the continental shelf and slope of Tuscany and Latium (Italy), in the north-western Mediterranean. Cluster analysis was used to group samples with similar species composition in terms of abundance, biomass and frequency of occurrence. Results allowed the identification of four to five broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 12 publications
3
45
0
1
Order By: Relevance
“…Moreover, the comparison of our results with those obtained from the quantitative analysis of different taxonomic groups undertaken in other areas of the Mediterranean also shows that the bathymetric distribution of demersal resources, considered as a whole, is also more complex than those associations found within the separated groups of cephalopods, crustaceans and fishes (González and Sánchez, 2002;Maynou and Cartes, 2000;Demestre et al, 2000;respectively). On the other hand, our results are similar to those obtained from the analysis of the whole demersal macrofauna developed in the central (Biagi et al, 2002;Colloca et al, 2003) and eastern (Kallianiotis et al, 2000) Mediterranean, which identified assemblages on the coastal shelf, middle shelf, shelf-edge, shallow upper-slope and deep upper-slope.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, the comparison of our results with those obtained from the quantitative analysis of different taxonomic groups undertaken in other areas of the Mediterranean also shows that the bathymetric distribution of demersal resources, considered as a whole, is also more complex than those associations found within the separated groups of cephalopods, crustaceans and fishes (González and Sánchez, 2002;Maynou and Cartes, 2000;Demestre et al, 2000;respectively). On the other hand, our results are similar to those obtained from the analysis of the whole demersal macrofauna developed in the central (Biagi et al, 2002;Colloca et al, 2003) and eastern (Kallianiotis et al, 2000) Mediterranean, which identified assemblages on the coastal shelf, middle shelf, shelf-edge, shallow upper-slope and deep upper-slope.…”
Section: Discussionsupporting
confidence: 79%
“…Demersal fish, crustacean and cephalopod assemblages in the Mediterranean Sea have been widely studied along the western (Demestre et al, 2000;Abelló et al, 2002;González and Sánchez, 2002; and references cited therein), central (Biagi et al, 2002;Colloca et al, 2003) and eastern (Labropoulou and Papaconstantinou, 2000;Kallianiotis et al, 2000) coasts. As concerns the Balearic Islands, the available information is related to fish and crustacean assemblages on bathyal slope bot-SCI.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the species richness in the catches, only three species (horse mackerel, hake and tub gurnard) accounted for the majority of the biomass and the specimens caught. A very different picture is shown by bottom trawling on the same bottoms, where catches are characterised by a considerably higher species diversity but lower dominance (Biagi et al, 2002). The efficiency of the four mesh sizes did not show significant differences with respect to biomass, abundance catch rates or the total hake catch.…”
Section: Discussionmentioning
confidence: 92%
“…According to the data series provided by FAO, a total of 21000 tonnes of hake was landed in this area in 2002(FAO, 2005. This species is the twelfth most abundant in overall landings (1.6% of the total Mediterranean landing) and the most abundant when only the demersal species are considered (Lleonart and Maynou, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…P. erythrinus is an important component of the upper shelf fish assemblage in the western Mediterranean Sea (Biagi et al 2002;Gaertner et al 2005) and specifically also in the southern Tyrrhenian Sea where the species is typical of the demersal fish community as deep as 100 m (Busalacchi et al 2010). Evidences of a differential distribution of fishing effort in the study area have been reported recently.…”
Section: Discussionmentioning
confidence: 99%